"What can I possibly do?": White individual responsibility for addressing racism as a public health crisis. (21st January 2022) - Liebow, Nabina K.; Rieder, Travis N.
Abstract: What responsibilities do individuals have when it comes to combating large‐scale public health crises such as racism? A seductive argument borrowed from the climate ethics literature suggests that focusing on individual morality for a structural problem such as racism is at best unhelpful and at worst actively harmful. In response, we argue that individuals have good moral reasons to modify their own behaviors to help in the fight against large, structural public health emergencies in general, and that the public health crisis of racism, in particular, demands heightened moral responsiveness from individual white people to resist white supremacy. The moral reasons that support white engagement in antiracist work extend above and beyond those regarding individual involvement in the fight against other collectively created public health challenges. Our conclusions help to defend the claim that racial literacy and antiracist education aimed at individuals are vital.